Language as a Tool Empowering Students to be Independent in Sociocultural Environment - Mereckaitė, Ingrida (Journal of Education Culture and Society, 2022)
Thesis. The aim of the research is to confirm the role of language as a tool empowering school students to act independently in educational activities and sociocultural environment. This can be achieved by encouraging students to actively participate in educational activities, to learn a language and other academic subjects without any direct input.Methods. The article is based on a scientific literature analysis and monitoring at one of the language integrated learning centres. It studies discussed hereof showcase the importance of language integration and a broader understanding of teaching students the basics of language skills.Results. The analysis shows language skills are a result (synthesis) of abilities and competencies combined by different disciplines and programmes. It is directly related to the methods, measures, situations and environments employed in educational activities. The studies discussed hereof showcase the importance of language integration and a broader understanding of teaching students the basics of language skills.Conclusion. Based on the research results it is possible to distinguish language as an independent learning tool. This is proven by such student skills as high motivation and inclusion; courage and self-confidence; ability to analyse, reason and summarise information; openness to learning; independence; curiosity; focus and concentration. The comparison of the data and the literature analysis allow concluding that this is one of the most resultative methods to develop the language skills of students in an integrated way.